CEO EDUCATION, INSTITUTIONAL OWNERSHIP, BOARD GENDER DIVERSITY AND MARKET UNCERTAINTY ON R&D INVESTMENT - Hendy Rizky Rummenigge; Sri Rahayu; Sundjoto Sundjoto (Jurnal Ekonomi, 2023)
To create a competitive advantage, companies must innovate by investing in R&D. R&D investment must be made to increase consumer interest and sustain the company’s business growth. Investment in R&D is influenced by various internal and external factors of the company, internal factors that are also related to corporate governance are CEO education, institutional ownership and board gender diversity, while external factors are market uncertainty. This study uses a quantitative approach that aims to determine the effect of CEO education, institutional ownership, board gender diversity and market uncertainty on R&D investment. The dependent variable is R&D investment, the independent variables are CEO education, institutional ownership, board gender diversity and market uncertainty, while the control variables are company size, ROA, and DAR. The research object is a manufacturing company listed on the Indonesia Stock Exchange for the period 2020 – 2022. The research sample is 30 manufacturing companies. The sampling technique used was purposive sampling. The analysis technique used is multiple regression. The results showed that CEO education and board gender diversity had a significant positive effect on R&D investment, while market uncertainty had a significant negative effect on R&D investment. Meanwhile, institutional ownership has no significant effect on R&D investment.